Using Minecraft to Develop Citizenship Competencies by Designing a Smart City: Fortaleciendo competencias ciudadanas a través del uso de Minecraft para crear una ciudad inteligente - Ortega Pérez, Paloma; Nieto Begné, Patricia Lorena; Cárdenas, Manuel Félix; Velázquez García , Lydia; Cedillo Hernández, Antonio (LATAM Revista Latinoamericana de Ciencias Sociales y Humanidades, 2025)
Serious-game environments have demonstrated efficacy in connecting theoretical concepts with practical application in university courses focused on social reform. This study assesses the influence of an immersive project in Minecraft: Education Edition on the enhancement of civic competencies and smart-city awareness among 28 undergraduate students participating in the “Citizenship and Smart Cities” course at Tecnologico de Monterrey (under TEC21 model), Campus Hidalgo, during the August–December 2024 semester. Through seven distinct phases, spanning community diagnosis to virtual urban redesign, students recognized tangible issues, devised contextually relevant remedies, and presented them via video walkthroughs of their Minecraft environments. Performance was evaluated using an institutional rubric, supplemented by a perception poll. Quantitative data indicate that 100% of students attained a proficient level in the “socially responsible solutions” (SEG0404); 82% achieved proficient and 3.5% outstanding levels in “critical reasoning” (SEG0503); and 75% attained proficient level in “strategic use of IT” (SEG0702). Survey data shown complete consensus that the unit promoted civic involvement, with 95% asserting that Minecraft enhanced their theoretical comprehension. Qualitative remarks confirmed increased social awareness and motivation. These findings endorse the incorporation of immersive, game-based methodologies to develop twenty-first-century civic competences in higher education.